DESIGN THINKING: AN APPROACH TO RESEARCH AND INNOVATION IN NURSING - Silva, Nubya Rodrigues da; Costa, Roberta; Locks, Melissa Orlandi Honório; Sebold, Luciara Fabiane (Cogitare Enfermagem, 2023)
Objective: To analyze the application of design thinking to the scientific production of a Postgraduate Nursing Program. Method: This is a documentary, descriptive, retrospective, and qualitative study of the scientific production of the Postgraduate Program in Nursing Care Management - Professional Modality, in Florianópolis, Santa Catarina, Brazil, from 2009 to 2022, based on dissertations published in a public directory. Results: Five academic master’s theses were analyzed that applied all or part of the design thinking approach to the development of proposed products/services. All the studies aimed to solve problems identified in the researchers’ professional contexts. The studies generated information, data, products, processes, and methodologies for nursing care. Conclusion: design thinking is an important reference point for nurses in the field of research and development, as well as contributing to the training of professionals who aim to solve complex problems in the field of health care, management, education, and research.